HMGB1 reduce DNA damage by binding KU70 to activate NHEJ pathway in colorectal cancer cells after radiation - Xiuxin Liu; Yuhui Han; Ruixue Kuang; Wenjiong Sheng; Yan Zhang; Xinyu Jia; Xiaoxiao Gao; Yanchao Ma (PLoS ONE, 2026)
DNA damage-induced by radiotherapy is a critical factor in promoting the death of colorectal cancer cells (CRC). Although high mobility group box 1 (HMGB1) reportedly plays a vital role in tumor radioresistance by modulating DNA damage repair, the precise mechanisms remain unclear. In this study, HMGB1 knockdown markedly enhanced cell apoptosis after radiation. HMGB1 downregulation significantly inhibited DNA damage repair and reactive oxygen species (ROS)-mediated redox homeostasis after irradiation in CRC cells. Mechanistically, HMGB1 interacts with KU70 via its region spanning residues 95–163. This interaction subsequently activates the non-homologous end joining (NHEJ) pathway to facilitate DNA damage repair, ultimately leading to reduced radiation-induced cell apoptosis. KU70 silencing showed the same effect as HMGB1 depletion mediated cell apoptosis and DNA damage response both in vitro and in vivo . Additionally, HMGB1 and KU70 were overexpressed in CRC tissues. Analysis of the GEPIA database indicated that elevated levels of both genes showed a trend toward association with poor patient prognosis, although this did not reach statistical significance. The current study revealed that HMGB1 may promote DNA damage repair through KU70 and its mediated NHEJ pathway to affect apoptosis in CRC cells after irradiation. Thus, targeting the HMGB1/KU70/NHEJ axis may be a potential therapeutic target to promote the response of CRC to radiotherapy and in-depth study of the specific mechanism of this axis in CRC radioresistance will help to the develop more effective treatment strategies.